Erythrocyte Indices MCV and/or MCH as First Round Screening Followed by Hb-analysis for β-thalassemia Carrier State - Edhyana Sahiratmadja; Ani Melani Maskoen; Lelani Reniarti; Delita Prihatni (The Prodia Education and Research Institute (PERI), 2022)
BACKGROUND: Being located in the global thalassemia belt area, Indonesia is estimated harboring about 10% thalassemia carriers; however, screening program is still diversely scattered across the country. Numerous erythrocyte indices have been introduced to help identifying thalassemia carriers with contradictory results. Therefore, this study had compared the use of mean corpuscular volume (MCV) and/or mean corpuscular hemoglobin (MCH) values and the most erythrocyte indices used in Indonesia which were Mentzer Index (MI) and Shine & Lal Index (SLI), as a first attempt in a mass screening for β-thalassemia carrier.METHODS: This was a retrospective study, evaluating laboratory data from family members of thalassemia major subjects. The sensitivity and specificity of MI and SLI were calculated. HbA2 >3.5% was used as a golden standard for β-thalassemia carrier and DNA examination was conducted to confirm β-globin mutation.RESULTS: Out of 160, 28.8% of the subjects had low Hb concentration. Interestingly, 79.4% of the subjects had low MCV and/or MCH with or without low Hb concentration. In this study, specificity and sensitivity of MI were 82.2% and 83.8%, whereas of SLI were 96% and 40.5%, respectively. Low MCV and/or MCH had covered IVS1nt5 and Cd26 mutation at β-globin gene; whereas MI and SLI had missed some samples, leading to false negative of thalassemia carrier results, when using MI or SLI only.CONCLUSION: MCV<80 fl and/or MCH<27 pg is the best first round mass screening method for β-thalassemia carrier in a limited facility area. However, Hb electrophoresis should be gradually installed regionally in various places wherever possible, as well as DNA analysis to confirm the mutation for an optimal carrier diagnosis.KEYWORDS: HbA2, HbE, iron deficiency anemia, Mentzer Index, Shine and Lal Index